2024
DOI: 10.3390/fermentation10020114
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Essential Oil Blends and Fumaric Acid on Ruminal Fermentation, Volatile Fatty Acid Production and Greenhouse Gas Emissions Using the Rumen Simulation Technique (RUSITEC)

Joel O. Alabi,
Peter A. Dele,
Deborah O. Okedoyin
et al.

Abstract: This study investigated the combined impact of essential oil blends (EOBs) and fumaric acid (FA) on ruminal fermentation in dairy cows using the rumen simulation technique (RUSITEC) system. Three rumen-cannulated, non-lactating Holstein Friesian cows served as inoculum donors. The substrate, a total mixed ration (TMR), comprised corn silage, alfalfa hay, and a concentrate mix in a 3:1:1 ratio. The four treatments evaluated were Control (TMR without additives), EFA1 (TMR + EOB1 + FA), EFA2 (TMR + EOB2 + FA), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
3

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 48 publications
1
4
3
Order By: Relevance
“…In the present study, the addition of GEO, MEO, and OLEO had no significant effect on CH 4 , CO 2 , NH 3 , and H 2 S production. This contradicts a previous study from our lab in which a combination of EOB containing garlic, lemongrass, cumin, lavender, and nutmeg and fumaric acid significantly reduced CH 4 gas emissions by 60% [26]. This could be attributed to the low dosage of EOB (3 µL/g) used in this present study, which is much lower (3 µL/g in the present experiment vs. 10 µL/g in the previous one) than that used in the previous study [26].…”
Section: Discussioncontrasting
confidence: 97%
See 3 more Smart Citations
“…In the present study, the addition of GEO, MEO, and OLEO had no significant effect on CH 4 , CO 2 , NH 3 , and H 2 S production. This contradicts a previous study from our lab in which a combination of EOB containing garlic, lemongrass, cumin, lavender, and nutmeg and fumaric acid significantly reduced CH 4 gas emissions by 60% [26]. This could be attributed to the low dosage of EOB (3 µL/g) used in this present study, which is much lower (3 µL/g in the present experiment vs. 10 µL/g in the previous one) than that used in the previous study [26].…”
Section: Discussioncontrasting
confidence: 97%
“…Monitoring gas production can provide insights into the dynamics of ruminal fermentation and the potential impacts of dietary interventions or feed additives. The lack of significant changes in gas production and effluent volume, in the present study, suggests that these interventions are safe for use in ruminant diets without causing adverse effects on rumen fermentation [26]. This observation is consistent with a previous study from our lab in which EOB and fumaric acid inclusion in the diets of dairy cows had no adverse effects on gas production [26].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Alternative products to conventional antibiotics, which serve as growth promoters in animal husbandry, have been investigated over the last two decades [6][7][8]. Studies have shown that various plant extracts, individual or essential oil blends (EOBs), probiotics, prebiotics, and algae rich in biologically active components can modify rumen fermentation, leading to decreases in the production of CH 4 and ammonia nitrogen in the rumen with mixed results [6,9,10]. The U.S. FDA has categorized some of these extracts as generally recognized as safe for human consumption [5,11].…”
Section: Introductionmentioning
confidence: 99%